The Graciousness, Tolerance and Affection in Al-Quran through A Value-Based Arabic Syntax - Mohd Nizwan Musling; Muhammad Zahid Ismai; Mohammad Najib Jaffar (Human Resource Management Academic Research Societ, 2024)
Indexed by ERA